2018
DOI: 10.1371/journal.pone.0206001
|View full text |Cite
|
Sign up to set email alerts
|

Profile of resistance to IVIG treatment in patients with Kawasaki disease and concomitant infection

Abstract: IntroductionKawasaki disease (KD) can be associated with concomitant viral or bacterial infections. Children with persistent or recurrent fever 36 hours after the end of intravenous immunoglobulin (IVIG) are considered to be resistant to treatment and are at increased risk for coronary complications. Although concomitant infection does not affect coronary outcome, it is unknown how it influences the response to IVIG treatment.MethodologyRetrospective cohort study between 2008 and 2016 in a tertiary pediatric u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 29 publications
0
20
3
Order By: Relevance
“…The low rate of patients with an aneurysm can be attributed to the low frequency of IVIG-resistant patients, as according to our results, 21% of the studied patients were resistant to IVIG, which is considered the main cause of aneurysm in treated patients (23). In the study by Tremoulet et al (24) in San Diego County, 38.3% of patients with KD were IVIG-resistant, which is much higher than the frequency of IVIG-resistant patients in our study, and in the study by Dionne et al (25), 24% of children were found to be IVIG-resistant, which is a little higher than the IVIG-resistance rate in our study (21%). This difference in the rates of resistance to IVIG can originate from different population characteristics, including age, serum levels of inflammatory markers, and liver enzymes, which have been suggested to affect the risk of resistance to IVIG (25).…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…The low rate of patients with an aneurysm can be attributed to the low frequency of IVIG-resistant patients, as according to our results, 21% of the studied patients were resistant to IVIG, which is considered the main cause of aneurysm in treated patients (23). In the study by Tremoulet et al (24) in San Diego County, 38.3% of patients with KD were IVIG-resistant, which is much higher than the frequency of IVIG-resistant patients in our study, and in the study by Dionne et al (25), 24% of children were found to be IVIG-resistant, which is a little higher than the IVIG-resistance rate in our study (21%). This difference in the rates of resistance to IVIG can originate from different population characteristics, including age, serum levels of inflammatory markers, and liver enzymes, which have been suggested to affect the risk of resistance to IVIG (25).…”
Section: Discussioncontrasting
confidence: 64%
“…In the study by Tremoulet et al (24) in San Diego County, 38.3% of patients with KD were IVIG-resistant, which is much higher than the frequency of IVIG-resistant patients in our study, and in the study by Dionne et al (25), 24% of children were found to be IVIG-resistant, which is a little higher than the IVIG-resistance rate in our study (21%). This difference in the rates of resistance to IVIG can originate from different population characteristics, including age, serum levels of inflammatory markers, and liver enzymes, which have been suggested to affect the risk of resistance to IVIG (25). Although concurrent infections are associated with KD, the clinical presentations, prognosis, and even response to IVIG treatment have been reported to be the same as in non-confirmed infectious patients (26).…”
Section: Discussioncontrasting
confidence: 64%
“…The vascular complications and responsiveness to IVIG in KD are largely related to the extent of KD inflammation, such as the degrees of concomitant infections and other inflammatory markers [29][30][31]. It is necessary to approach KD by considering the underlying disease and other inflammatory factors along with hematological Z-values.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the patients who have persistent or recurrent fever more than 24 hours after completion of the initial treatment should also be assessed for concomitant infection [6] or rare hemophagocytic lymphohistiocytosis [7]. Children with KD and concomitant infection are more likely to have persistent fever after treatment and this association increases the likelihood of receiving a second dose of IVIG but not the risk of coronary complication.…”
Section: Definition Of Ivig Resistancementioning
confidence: 99%